A proposal of a Balanced Scorecard for an environmental education program at universities. (20th January 2018) - de Andrade Guerra, José Baltazar Salgueirinho Osório; Garcia, Jéssica; de Andrade Lima, Mauricio; Barbosa, Samuel Borges; Heerdt, Mauri Luiz; Berchin, Issa Ibrahim
Abstract: By developing and implementing environmental concerns in its principles and infrastructure, universities are becoming increasingly active in promoting societal changes towards sustainable development. These environmental concerns are translated into comprehensive and transversal environmental education programs aimed at building capacities and promoting awareness not only for students but also to the surrounding communities. This paper aims to develop a Balanced Scorecard strategy map for implementing and monitoring environmental education programs in universities. To accomplish this objective, we conducted a literature review on environmental education in higher education, finding 10 primary indicators and 40 sub-indicators needed to implement environmental education programs in universities. Fifteen experts in sustainability research were asked to evaluate these indicators and sub-indicators. Then, those indicators and expert evaluations were used to build a decision tree that supports the Balanced Scorecard. Based on our findings, we created and adapted a strategy map for environmental education based on five dimensions: sustainable development; environmental education; teaching processes and environmental management; learning and environmental growth; and economic and financial responsibility. The main contribution of this paper is to propose a theoretical proposal that can serve as a guide to implement and monitor environmental education programs in universities.